PENGARUH TEKNOLOGI INFORMASI, REMUNERASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI KOTA MEDAN - Yola Yolanda; Dessyana Dessyana (FIRM Journal of Management Studies, 2022)
The development is marked by the development of information technology. The longer humans can’t be separated from technology. Information technology products are developing very rapidly, adapting to human needs. Various products from information technology make it easier in every process, so it can save time. The use of information technology is strongly influenced by the success, quality and quantity of performance in an organization. employee performance is a process of assessing work against predetermined goals and objectives, including information on the efficiency of resource use in producing goods and services, quality of goods, results of activities compared to what is desired. There are several factors that can affect employee performance, namely information technology, remuneration and work motivation. The purpose of this research is to analyze the effect of information technology, remuneration, work motivation on employee performance. This type of research, including causality research, is to examine causal relationships. This research was started by distributing questionnaires to Medan City employees with a sample of 100 Medan City employees. This type of research data is primary data because it is carried out by means of field studies using questionnaires. Data analysis was carried out using SPSS 25 software tools